To solve the equation \((x - 6)^2 = 51\) using square roots, follow these steps:
-
Take the square root of both sides:
\[ x - 6 = \pm \sqrt{51} \]
-
Calculate \(\sqrt{51}\):
The square root of 51 is approximately \(7.14\) (when rounded to the nearest hundredth).
-
Set up both equations:
\[ x - 6 = \sqrt{51} \quad \text{and} \quad x - 6 = -\sqrt{51} \]
-
Solve the first equation:
\[ x - 6 = 7.14 \] \[ x = 7.14 + 6 \] \[ x \approx 13.14 \]
-
Solve the second equation:
\[ x - 6 = -7.14 \] \[ x = -7.14 + 6 \] \[ x \approx -1.14 \]
Thus, the solutions to the equation \((x - 6)^2 = 51\) are:
\[ x \approx 13.14 \quad \text{and} \quad x \approx -1.14 \]